2021
DOI: 10.1177/08850666211043436
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Tracheostomy: Experience in a University Hospital With Intermediate Follow-up

Abstract: The benefits of percutaneous dilational tracheostomy (PDT) placement have been well documented in patients requiring prolonged mechanical ventilation. However, the data regarding the benefit of PDT in coronavirus-2019 (COVID-19) patients are scarce. The objective of this study is to evaluate the outcomes of a cohort of 37 patients who underwent tracheostomy as part of their COVID-19 care. Retrospective data from a series for 37 patients undergoing tracheostomy was collected using chart review. Primary outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…All COVID-19 patients were treated with PDT; none of the medical team was infected due to the procedure. The rate of complications was similar to other patient groups, and PDT can therefore be considered safe for COVID-19 patients, which is in line with the results of other studies [ 26 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…All COVID-19 patients were treated with PDT; none of the medical team was infected due to the procedure. The rate of complications was similar to other patient groups, and PDT can therefore be considered safe for COVID-19 patients, which is in line with the results of other studies [ 26 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…Meyer et al reported bronchoscope guided PDT decreased the risk of bleeding in comparison to open tracheostomies, considering the high rate of anti-coagulation therapy required for these patients. Guided PDT reduced transmission of virus to HCWs from critically ill COVID-19 patients [15, 68-69], although there was no major difference in complication rate in PDT compared to open tracheostomy [64, 61]. However, in a pre-COVID study demonstrated that use of bronchoscopes did not affect the overall outcome in patients with open or percutaneous tracheostomy [70].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic and interventional bronchoscopy is an effective procedure utilized in severe or critically ill ICU admitted patients [12][13][14][15]. The use of therapeutic bronchoscopy was mainly used for the indications like acute lung failure, atelectasis, hyperaemia, routine clearance of obstructive airway in patient with lung transplantation due to COVID-19 pneumonia [16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…53 54 In a recent study of 37 patients with COVID-19 undergoing tracheostomy, 35 were alive at 60 days of postplacement, 33 weaned from mechanical ventilation, and 18 decannulated. 55…”
Section: Tracheostomy In Covid-19mentioning
confidence: 99%